Pengendalian Internal Terhadap Deteksi Risiko Kecurangan dan Kinerja Perusahaan Daerah Air Minum - Ardianto, Yuli; Riskarini, Dian (Jurnal Manajemen, 2016)
ABSTRACT The research was entitled The influence of Internal Control on Risk Management and its implication on Perusahaan Daerah Air Minum Performance. The formulation of the problem is whether there: internal control influence on enterprise risk management, internal control influence on corporate performance, fraud influence on corporate performance. The purpose of this study is to examine and analyze: internal control influence on enterprise risk management, internal control influence on corporate performance, fraud influence on corporate performance. During this time many research fields of accounting and finance are well have analyzed the influence of the internal control on risk management and corporate performance, but rarely all three studies measure the impact of these variables on corporate performance as measured by Malcolm Baldrige. The research method uses analytical descriptive and exploratory. Samples were directors and audit committee in PDAM Jakarta, Bogor, Tangerang and Bekasi. Methods of data analysis using partial least square. Results of the study are: internal control positive effect on the risk management, internal control positive effect on the malcolm baldrige performance, risk management positive effect on the malcolm baldrige performance